‫أثر استخدام‬ ‫الموازنات‬ ‫التخطيطية‬ ‫على‬ ‫عمليتي‬ ‫التخطيط‬ ‫و‬ ‫الرقابة‬ ‫‪-‬‬‫دراسة‬‫ميدانية‬ ‫لع‫ينة‬‫من‬ ‫المؤسسات‬ ‫االاقتصادية‬ ‫الجزائرية‬ - ‫فؤاد ‬‫جبابلية‬; ‫عبد‬‫الرحمان‬ ‫نوري‬ (My University, 2019)
Abstract The study aims to determine the role of planning budgets in the Algerian economic institutions and the extent of their contribution to the planning and control processes. A field study of a sample of Algerian economic institutions was based on the collection and analysis of data after the questionnaire was prepared and using the SPSS program. The study reached a number of results, the most prominent of which is that the planning budgets are used in the institutions under study for planning at a lower rate than for supervision, and that the control function is necessary for the success of the planning and is based on the errors found in the plan of the institution. Among the most important recommendations of the study, An information system that helps to prepare more realistic estimates on the basis of sufficient and appropriate information. The budget period must be divided into supervisory periods that monitor and evaluate the performance of the institutions. ‬